Evangelical postcolonial conversations: global awakenings in theology and praxis - Smith, Kay Higuera (IVP Academic, 2014)
Introduction : why postcolonial conversations matter -- Reflection on postcolonial friendship Brian D. McLaren -- The importance of postcolonial Evangelical conversations Steve Hu -- A response to the postcolonial challenge to Evangelicas Editors -- Prospects and problems for Evangelical postcolonialisms Robert S. Heaney -- Part I. Mission and metanarrative origins and articulations -- ch. 1. From good, "the only good Indian is a dead Indian" to better, "kill the Indian and save the man" to best, "old things pass away and all things become white!" : an American hermeneutic of colonization L. Daniel Hawk and Richard L. Twiss -- ch. 2. North American mission and motive : following the markers Gregory Lee Cueller and Randy S. Woodley -- ch. 3. Postcolonial feminism, the Bible and the native Indian women Jayachitra Lalitha -- ch. 4. Converting a colonialist Christ : toward an African postcolonial Christology Victor Ifeanyi Ezigbo and Reggie L. Williams -- Part II. the stories behind the colonial stories -- ch. 5. Tracing the metanarrative of colonialism and its legacy Teri R. Merrick -- ch. 6. American exceptionalism as prophetic nationalism Kurt Anders Richardson -- Part III. Revisioning Evangelical theology -- ch. 7. The apocalypse of colonialism : notes toward a postcolonial eschatology Christian T. Collins Winn and Amos Yong -- ch. 8. Jesus/Christ the hybrid : toward a postcolonial Evangelical Christology Joya Colon-Berezin and Peter Goodwin Heltzel -- ch. 9. Recovering the spirit of Pentecost : canon and Catholicity in postcolonial perspective /Megan K. DeFranza and John R. Franke -- Part IV. Transforming the Evangelical legacy -- ch. 10. The problem and promise of praxis in postcolonial criticism Gilberto Lozano and Federico A. Roth -- ch. 11. Embracing the other : a vision for Evangelical identity Kay Higuera Smith -- ch. 12. Healthy leadership and power differences in the postcolonial community : two reflections Nicholas Rowe and Ray Aldred -- ch. 13. Christian disciplines as ways of instilling God's shalom for postcolonial communities : two reflections Nicholas Rowe and Safwat Marzouk -- Part V. Closing the circle -- ch. 14. Hosting a true roundtable : diaogue across theological and postcolonial divides Judith Oleson -- Benediction Gregory W. Carmer -- Dr. Richard Twiss, a remembrance Randy S. Woodley